(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The article proposes a linguistic analysis of the Italian law on informed consent and advance healthcare directives (or living wills). The study investigates the stylistic features of the legal text. The analysis examines how the contents are organised within the text and considers the vocabulary regarding its accessibility. A further question concerns who the law is addressed to and explores what political message is conveyed.